BRIDGING CULTURES: THE LINGUISTIC LANDSCAPE OF PESANTREN AND ITS CULTURAL DIVERSITY - Yusuf, Kamal (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This article delves into the rich tapestry of cultures and languages within Islamic pesantren, traditional Islamic boarding schools in Indonesia. It examines the linguistic landscape of pesantren and its role in fostering cultural diversity. The focal point is the intricate interplay of various languages within the pesantren environment, including Arabic, the language of religion, Indonesian, the national language, and a myriad of local dialects and languages. Through qualitative analysis, the study explores how linguistic diversity reflects and contributes to the broader cultural mosaic within pesantren. It sheds light on how the use of different languages shapes social interactions, educational practices, and identity formation within these institutions. Moreover, the article discusses the dynamic nature of cultural diversity within pesantren, influenced by historical, geographical, and sociopolitical factors. By unpacking the complexities of language use and cultural diversity, this research offers insights into the multifaceted nature of pesantren as hubs of cultural exchange and preservation. Understanding the linguistic landscape and cultural diversity within pesantren is crucial for appreciating the richness of Indonesia’s Islamic educational tradition and its significance in shaping national identity.